Educação e constituinte: os debates nas audiências públicas da Subcomissão da Educação, Cultura e Esportes (1987) - Sanchez, Isabela (2021)
This research aims to analyze the groups that participated in the public hearings for education carried out by the National Constituent Assembly Subcommittee on Education, Culture and Sports (Assembleia Nacional Constituinte, ANC) in 1987, placing them ahead of the debates and general themes, in order to understand how they provoked and conducted the educational theme based on their propositions, organization and influences. The research also seeks to explore the Subcommittee’s institutionalization, functioning and format processes, in order to understand the role of these subjects within the composition of the existing political forces with regard to the dynamics between the legislative and the constitutional text drafting. The main sources of this study are the Education Subcommittees session drafts published in the ANC Annals and diaries. Antonio Gramsci's theoretical contributions were applied in order to characterize and analyze agent roles, the transition to democracy and the search for consensus aiming to examine the current tension between civil society and institutional politics. The investigation pointed to the pluralism of groups generally shown to be cohesive within the process and to the centrality of themes prevailing in the Federal Constitution of 1988 based on the hegemony established in the debates